A Study of Part-Time Worker Students at the Postgraduate Level - Khanal, Basudeb (Bouddhik Abhiyan (बौद्धिक अभियान), 2022)
This paper attempts to analyze a study of part-time worker students at the postgraduate level in economics education in Kathmandu valley. The students who continue their postgraduate studies and jobs are known as part-time working students. This paper is based on a qualitative research design. Data were collected from in-depth personal interviews. For this purpose, four students were purposively selected covering gender from the first and second semesters. This paper has two-fold findings: most students engage in part-time work to gain thirst and survival and develop future working experience in the second. However, both types of students reported that part-time jobs support a lower survival level, which has disrupted their study. Furthermore, both types of students involved in part-time work do not seem satisfied with their job and study.